Concerns About Automation and Negative Sentiment Toward Immigration. (August 2020) - Gamez-Djokic, Monica; Waytz, Adam
Across 12 studies ( N = 31, 581), we examined how concerns about the rise of automation may be associated with attitudes toward immigrants. Studies 1a to 1g used archival data ranging from 1986 to 2017 across both the United States and Europe to demonstrate a robust association between concerns about automation and more negative attitudes toward immigrants. Studies 2a, 2b, 2c, and 3 employed both correlational and experimental methods to demonstrate that people's concerns about automation are linked to increased support for restrictive immigration policies. These studies show this association to be mediated by perceptions of both realistic and symbolic intergroup threat. Finally, Study 4 experimentally demonstrated that automation may lead to more discriminatory behavior toward immigrants in the context of layoffs. Together, these results suggest that concerns about automation correspond to perceptions of threat and competition with immigrants as well as consequent anti-immigration sentiment.